The Impact of the Development of the INA Marina Beach Tourism Area on the Socio-Economic Life of the Surrounding Communities - SALAMPESSY, Zainab; SANGADJI, Maryam; MATITAPUTTY, I. T. (PT Keberlanjutan Strategis Indonesia, 2024)
The development of an area that has the potential to become a tourist area is a huge opportunity, not only can it beautify the face of the city, but it can also have an impact on the economy of the surrounding community, and can improve the tourism sector in the area. It is hoped that the development of the Ina Marina beach area as a tourist area will have a positive impact not only on regional income. However, it can be directly beneficial to the economy of the surrounding community. This research aims to determine the impact of developing the Ina Marina Beach tourist area on the socio-economic life of the surrounding community and the strategies carried. This research uses a qualitative descriptive research method. Data collection was carried out through literature study, observation, and interviews. Data were analyzed using the Miles and Huberman model analysis. The research results show that the impacts felt by the community related to the development of the Ina Marina Beach tourist area are changes in lifestyle, job diversification, economic improvement, and job opportunities.